Competency Based Approach between Theory and Practice - BADER, Faiza; HAMADA, Hacene (Journal of Human Sciences, 2015)
This paper purports to investigate the extent to which pre-service middle school teachers of English at the Teachers Training School of Constantine (ENSC) are able to put into practice the Competency based approach (CBA) tenets. A sample population of 42 pre-service middle school teachers took part in the study through a survey which revealed that a gap exists between the theoretical framework of the CBA gained in the school, and the practical implementation of that knowledge. Thus, more efforts should be spent to ensure a better teacher quality and training at the level of the school.